THE EFFECT OF CONCEPT MAPPING COMBINED WITH STUDENTS’ PRESENTATION METHOD ON STUDENTS’ ACHIEVEMENT IN MACROECONOMICS COURSE - Sunaryanto, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Research on concept mapping method has been conducted in colleges and has indicated some advantages of the method. However, it is rarely the method is combined with another method of teaching to increase its effectiveness in increasing students’ performance. The study aims to explain the effectiveness of integration of concept mapping method into classroom presentation and discussion in macroeconomics course. The participants were 156 students who took macroeconomics course at Economics Faculty of a University in East Java Indonesia. Quasy experiment is used as design of the research. By using t-Test in analyzing collected data, the result of the research shows that students taught with concept mapping method combined with student’s presentation method get the higher academic achievement to compare with students taught with students’ presentation and discussion method of teaching. This has the implication that students’ presentation method of teaching followed by concept mapping method can increase students’ achievement.